The Review on Electrospun Gelatin Fiber Scaffold - Zhan, Jianchao; Lan, Ping (Journal of Research Updates in Polymer Science, 2013)
The fabrication of the Guided Tissue Regeneration (GTR) membrane materials have become the key technique of the tissue engineering scaffold study. The cells adhere well on the fibers whose dimension is below their own so that the porous three dimension scaffold material can mimic the strueture of the natural extracellular matrix better and have the potential to be an ideal GTR membrane material. Gelatin, a kind of protein obtained from hydrolyzed and denatured animal skin, is a condensation polymer of a variety of amino acids and so it is a kind of bio-polymer with good water-solubility. Gelatin fiber mats with submicro and nanometer scale can simulate extracellular matrix structure of the human tissues and organs and can be used widely in the tissue engineering field because of their excellent bio-affinity. Electrospinning is a very attractive method for preparing polymer or composite nanofibers and so electrospinning technique was developed to prepare nanofibrous gelatin matrix. The electrospun of gelatin to fabricate the scaffold material has obtained more attention recently because of its biocompatibility, high surface area-to-volume ratio, degradability and less immunogenic property. The structure and performance of the electrospinning gelatin fiber mats which were manufactured by different solvents, electrospinning process, cross-linking process were reviewed. The properties and application of the two-component and multicomponent gelatin fiber mats were analyzed.